Modeling and optimization of microwave ring resonator filters using CST software - Zhu, Zhongdao (2013)
The thesis reports on modeling two types of bandpass microwave filters that use dielectric resonator for filtering of the signal. The instance modeling is done using a commercial CST software package The thesis introduces the CST software package and outlines the approach of modeling of two filters. Then tested CST meshing properties and simulation results. The first model is a dielectric ring loaded on substrate excited by microstrip lines. The second model has two dielectric rings loaded in a metal box which is filled with foam. The impact of different mesh sizes is investigated on the convergence of S-parameters, in particular their characteristics at center frequency. Many simulations have been done to find out the relationship between physical parameters, such as the radius of the outer ring, and the S-parameters. The CST software is also used to optimize characteristics of filters by changing the critical parameters. The patterns of e-field and h-field are been compared and analyzed to modify the structure of the dielectric ring resonator filter. The newly developed CST's Perfect Boundary Approximation (PBA) and FPBA solver is tested to prove their quality. Based on simulation data, a guess is proposed to revise the simulation result to get better accuracy.